The growing importance of consumer finance for financial inclusion in India - Saon Ray; Smita Miglani; Sandeep Paul (Indian Council for Research on International Economic Relations (ICRIER), 2018)
Financial inclusion or access to financial services is a major development goal for all nations across the globe. The concept has a multitude of dimensions from payments and savings accounts, credit, insurance and pensions and securities market. Ensuring quality access to formal financial services has always been a challenging task. Despite being a prime policy agenda for decades, the goal of universal financial inclusion is yet to be achieved in India. The Indian financial inclusion story so far was led by commercial banks and MFIs. While acknowledging the importance of access to credit for productive purposes, a total integration with financial market also means access to services like insurance and consumption loans. This paper examines the role of consumer finance, a high growth segment of the Indian financial sector in promoting financial inclusion. Consumer finance involves granting credit to consumers to enable them to possess goods for everyday use. While the Indian financial sector is changing rapidly, a large number of households still rely on informal sources for unforeseen expenditure. The paper presents results of a survey of consumer perception on the role of consumer credit to financial inclusion.
Keywords: G23; G38; 330; financial inclusion; NBFCs; consumer survey